2012
DOI: 10.1074/jbc.m112.375725
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Peptidylarginine Deiminase (PAD) Inhibitors Regulate the Autophagy Flux and the Mammalian Target of Rapamycin Complex 1 Activity

Abstract: Background: Histone citrullination by PAD4 regulates tumor suppressor gene expression. Results:The novel PAD inhibitor YW3-56 inhibits cancerous growth by perturbing autophagy and regulating the SESN2-mTORC1 signaling axis. Conclusion: YW3-56 regulates the SESN2-mTORC1 autophagy pathway as one of its anticancer mechanisms. Significance: This study identifies a novel function of PAD4 in the autophagy pathway and developed potent PAD inhibitors for future cancer research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
150
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(158 citation statements)
references
References 60 publications
5
150
0
Order By: Relevance
“…Moscarello et al [16] showed that 2-CA, which is a small molecule PAD inhibitor, attenuated disease symptoms in EAE models of MS. In addition, YW3-56, which is a novel PAD inhibitor, was shown to inhibit cancer growth effectively and induce autophagy in a cancer cell line [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moscarello et al [16] showed that 2-CA, which is a small molecule PAD inhibitor, attenuated disease symptoms in EAE models of MS. In addition, YW3-56, which is a novel PAD inhibitor, was shown to inhibit cancer growth effectively and induce autophagy in a cancer cell line [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some classes of compounds have been described to inhibit PADI4 [558][559][560][561]. There are several available crystallographic structures of these enzymes, also in complex with inhibitors (PDB codes: 1WD8, 1WD9, 1WDA, 2DEW, 2DEX, 2DEY, 2DW5, 3APM, 3APN, 3B1T, 3B1U and 4DKT) [560][561][562][563].…”
Section: Citrullination/deiminationmentioning
confidence: 99%
“…Cl-amidine can also suppress colitis by driving apoptosis of inflammatory cells and is a candidate therapeutic drug for inflammatory bowel diseases [75,76]. YW3-56 is identified as a novel PADI4 inhibitor, and SESN2 is one of the YW3-56 target genes which encodes an upstream inhibitor of the mammalian target of rapamycin complex 1 signaling pathway [77].…”
Section: Padi4 and Rheumatoid Arthritismentioning
confidence: 99%